2004
DOI: 10.1093/carcin/bgh295
|View full text |Cite
|
Sign up to set email alerts
|

Arsenite induces prominent mitotic arrest via inhibition of G2 checkpoint activation in CGL-2 cells

Abstract: Arsenic compounds, which are well-documented human carcinogens, are now used in cancer therapy. Knowledge of the mechanism by which arsenic exerts its toxicity may help in designing a more effective regimen for therapy. In this study, we showed that arsenite could induce prominent mitotic arrest in CGL-2 cells and demonstrated the presence of damaged DNA in arsenite-arrested mitotic cells. We then explored why these cells with arsenite-induced DNA damage were arrested at mitosis instead of G2 stage. When synch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 44 publications
6
45
1
Order By: Relevance
“…Another group has also shown that arsenic treatment induces the phosphorylation and nuclear accumulation of histone H2AX (28). However, our data indicated the colocalization and direct involvement of TOPK in As 3+ -induced apoptosis.…”
Section: Discussioncontrasting
confidence: 62%
“…Another group has also shown that arsenic treatment induces the phosphorylation and nuclear accumulation of histone H2AX (28). However, our data indicated the colocalization and direct involvement of TOPK in As 3+ -induced apoptosis.…”
Section: Discussioncontrasting
confidence: 62%
“…Although the linkage between p53 mutation and arsenic exposure is not clear, the affect of arsenic on p53 regulation is well documented. Both in vitro and As-BD lesion studies indicated that arsenic exposure was associated with G2/M cell cycle arrest and DNA aneuploidy [88][89][90]. These cellular abnormalities may associate with p53 dysfunction induced by arsenic.…”
Section: Pathomechanisms Of Arsenic-induced Bowen's Diseasementioning
confidence: 99%
“…Arsenite is a mitotic disruptor causing mitotic arrest and subsequent apoptosis in SV40-transformed human fibroblast (States et al, 2002), TR9-7 cells , HeLa, KB (Huang and Lee, 1998), CGL-2 (Yih et al, 2005), and U937 (McCabe, Jr. et al, 2000;McCollum et al, 2005) cells. The mechanism through which arsenite causes mitotic arrest is highly disputed.…”
Section: Introductionmentioning
confidence: 99%